Low Lactose Milk (LLM) on Refeeding of Infantile Diarrhoea - Suharjono Suharjono; Sunoto Sunoto; Aswitha Boediarso; Sutoto Sutoto; Dadi E. M. (Paediatrica Indonesiana, 1975)
Seventeen infants suffering from diarrhoea hospitalized in the Department of Child Health, Medical School University of Indonesia/Dr. Tjipto Mangunkusumo General Hospital from 10 to 31 August 1973 were refed with LLM, Almiron or SGM. LLM gives good to excellent results in refeeding of infants suffering from diarrhoea. Nine out of 17 cases were refed with LLM, where as the other 8 with Almiron or SGM as a control. Result of LLM in stopping diarrhoea was excellent in 5, good in 2, poor in 2 cases. Increase of body weight was excellent in 4 cases, good in none, poor in 5 cases. Results of Almiron or SGM in stopping diarrhoea was excellent in 1 case, good in one, poor in 6 cases. Increase of body weight was excellent in 1 case, good in none, poor in 7 cases. From these results it is recommended to give low lactose milk as refeeding on patients with infantile gastroenteritis.